2018
DOI: 10.1016/j.jcte.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific correlation of intranodular chronic lymphocytic thyroiditis with thyroid nodule size, echogenicity, and histologically-verified cytological class of malignancy risk

Abstract: No data are available on the cytologically and histologically demonstrated presence of intranodular chronic lymphocytic thyroiditis (ICLT) and on the ICLT relationship with thyroid nodule characteristics such as size, echotexture and nature (benign or malignant). We wished to fill this gap by analyzing data in a gender-specific fashion. We studied 408 thyroid nodules from 408 consecutive persons (325 females and 83 males). Nodules were isoechoic (n = 268) or hypoechoic (n = 140), ICLT +ve (n = 113 [27.7%]) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…As mentioned in the Introduction, in the same cohort of patients of the present study, we have previously found that the presence/ absence of ICLT is associated with some sexually dimorphic characteristics of thyroid nodules [7]. One previous finding was that ICLT + ve hypoechoic nodules of females and ICLT-ve hypoechoic nodules of males had the greatest rate of histologically verified malignancy (67 % both), while ICLT-ve isoechoic nodules of females had the lowest (19 %).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As mentioned in the Introduction, in the same cohort of patients of the present study, we have previously found that the presence/ absence of ICLT is associated with some sexually dimorphic characteristics of thyroid nodules [7]. One previous finding was that ICLT + ve hypoechoic nodules of females and ICLT-ve hypoechoic nodules of males had the greatest rate of histologically verified malignancy (67 % both), while ICLT-ve isoechoic nodules of females had the lowest (19 %).…”
Section: Discussionsupporting
confidence: 75%
“…In our clinical practice on thyroidectomized patients, we have noticed that when the presence of lymphocytic infiltration of the FNA-interrogated nodule had been mentioned in the cytological report, this had a different predictive value for malignancy depending on echotexture and gender [7]. For instance, nodules containing a lymphocytic infiltrate, having the same echotexture (hypoechogenicity) and belonging to the same FNA category (follicular neoplasm [FN] or suspicious for a follicular neoplasm [SFN]), had a relatively low risk of malignancy if the patient was male, but a very high one if the patient was female [7]. As well known, the detection of lymphocytic infiltration in the FNA-interrogated thyroid nodule (see below, Patients and Methods) and the ensuing diagnosis of chronic lymphocytic thyroiditis is just used to categorize the nodule as benign if there are no other associated cytological signs of malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto’s thyroiditis (HT), also known as chronic lymphocytic thyroiditis (CLT), interfere with the accurate cytological diagnosis of thyroid nodules ( 8 ), although CLT is diagnosed based on the pathologic findings in principle. CLT is characterized with enlarged nuclei as well as lymphocytic and plasma cell infiltration, and lesions of CLT vary in intensity from one part of the gland to another, which may complicate the preoperative diagnosis of thyroid nodules ( 3 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 Chronic lymphocytic thyroiditis (CLT) is an insidious inflammation of the thyroid gland that is known to increase cytologic atypia on FNA. 8 This disease process may microscopically resemble AUS/FLUS with cytologic findings of enlarged nuclei, lymphocytic and plasma cell infiltration, atrophic follicles with abundant oncocytes and often atypical epithelium. 1,6,7 As CLT progresses, features unique to this entity can be observed on final pathology (e.g., fibrosis, nodularity, atrophic parenchyma).…”
Section: Introductionmentioning
confidence: 99%